A comparison between OSv unikernels and Docker containers as building blocks for an Internet of Things platform - FRAGA, Vinícius Matos da Silveira (2019)
The Internet of Things (IoT) growth has been stimulating the development of novel technology to better fulfil its requirements. Due to its scale, IoT is powered by distributed, horizontally scalable systems, such as service oriented architectures and cloud computing. In this context, a potentially cheaper, safer and more efficient approach to virtualisation in the cloud could be the unikernel model. A unikernel is a single-process binary made of a kernel and an application built together, therefore fitting into microservice architectures, and capable of lowering computational costs in terms of time and space per service. The objective of this work is to analyse how viable it would be to develop an IoT platform meant to run on unikernels, as well as evaluate and compare unikernels’ performance to containers. In order to do so, a microservice IoT platform was proposed and deployed to OSv unikernel and Docker containers to work as a benchmark. Results show that it is possible to deploy modern solutions to unikernels, while highlighting open challenges and issues. Also, the expected performance gains of unikernels cannot be yet generalised, as in many cases they are still surpassed by containers.